Усовершенствование рекуперативного воздухонагревателя для расширения области его применения при условии использования запыленного теплоносителя - Юрко, Владимир Владимирович; Ганжа, Антон Николаевич (НТУ "ХПИ", 2018)
Рассмотрены вопросы использования тепла дымовых газов для нагрева воздуха горения. Разработанная конструкция петлевого воздухонагревателя, позволяющая работать на запыленном греющем теплоносителе. Приведенная сравнительная характеристика схем движения теплоносителей и выбрана оптимальная конструкция, позволяющая продлить строк эффективной службы теплообменного аппарата. Предлагаемая конструкция петлевого воздухонагревателя дает возможность не только утилизировать вторичное тепло дымовых газов для нагрева воздуха горения, но и решить проблемы, связанные с эффективной работой воздухонагревателя на запыленном теплоносителе, улавливать ценную пыль технологических процессов.

The aim of the work is the development of highly efficient heat exchange equipment with an optimal flow of heat transfer media for heating air with the smudged flue gases that are released during various technological processes. To achieve this goal, the following work was used in the work: calculation methods for studying heat transfer; physical modeling of heat transfer processes; methods of mathematical statistics; methods of the theory of similarity; mathematical modeling of heat exchange between flue gases and air through loop tubes using an object-oriented programming environment Borland C++ Builder. The obtained results show that, with the correct choice of the coolant flow pattern, it is possible to heat air up to 500 ºС with a dusty coolant. The choice of the optimum design of the recuperator allows prolonging the period of effective operation. Advantage of the heater of the proposed design is the ability to carry out a stable heating of the combustion air, catching process dust, and prolong the effective operation of the air heater. The results of the solution of the tasks set in the work can be used to develop energy-saving complexes in the sphere of metallurgy and power engineering, for the development of energy-efficient complexes, highly efficient heat exchange equipment and systems for utilization of thermal secondary energy resources of high-temperature energy technological processes.
Improving recuperative air heater to enlarge its application area provided that the dust-laden heat carrier is used
Keywords: петлевой воздухонагреватель; использование вторичного тепла; нагрев воздуха; схема движения теплоносителей; магнитно-импульсная очистка; газо-импульсная очистка; loop air heater; dusty coolant; coolant flow chart